Policy Implications of the Effect of Multimarket Contact on Airfares in China's Aviation Market - Chai, Yidan (Université d'Ottawa | University of Ottawa, 2014)
China’s civil aviation has experienced tremendous growth since the deregulation in 1978. Especially after the merger in 2002 and 2004, the multimarket contact among airlines increased. The paper examines the effects of multimarket contact under the conditions of asymmetric territorial interests on airfares during the period 2nd June – 22nd June 2014 in China’s civil aviation. The results show that the multimarket contact has limited effect on airfare. However, the government regulatory polices have more significant effect on airfares. Although Chinese government has deregulated the civil aviation industry in the past three decades, it has been careful to limit the pace and scope of deregulation so that ultimate control of the industry remains firmly with the state. Under this condition, the pricing behavior of airlines has been partially weakened and thus the effect of multimarket contact is not significant enough in China’s civil aviation. The analysis results reveal that civil aviation market in China is still away from completely free market.